The impact of inflation on the personal income tax burden - Marcin Burzec (Acta Iuris Stetinensis)
In the design of personal income tax, it is important that, in addition to the proper formation of its individual design elements, the legislator also takes care of their adequate protection against inflation. The absence of such regulation leads to a disproportionately high fiscal burden. This is due to the fact that often the design elements of the tax are expressed in terms of amounts. Thus, the lack of indexing mechanisms in income tax leads to erosion of nominally expressed design elements. This undermines the fair burden of this tax. The purpose of this article is to analyse how legal regulations safeguard proper protection of taxpayers against erosion of nominally established design elements of the Polish personal income tax. With relatively low inflation for more than two decades, this problem had not been noticeable. Only the high inflation rate in the European Union has once again drawn attention to this very important issue.